Laura architecture: towards a simpler way of building situation-aware and business-aware final WSN/IOT applications - Teixeira, Sergio (2019)
The explosion of smart objects made companies rethink their Business Model (BM) using Wireless Sensor Networks (WSN) and the Internet of Things (IoT) aiming to improve their Business Processes (BP) to achieve competitiveness. Business environments are complex due to the wide variety of technologies, hardware and software solutions that compose heterogeneous enterprise environments. On the other hand, putting real-world IoT scenarios into practice is still a challenge for even experienced developers, because it requires low level programming skills and, at the same time, specific domain knowledge of a company`s BM. This thesis proposes LAURA - Lean AUtomatic code generation for situation-aware and business-awaRe Applications, a flexible, service-oriented and general open source conceptual architecture, designed to support the deployment of decoupled IoT applications. An empirical evaluation has shown that LAURA simplifies the development of final Situation-Aware or Business-Aware applications, reducing the need for specialized IoT low level knowledge, while showing an acceptable performance. LAURA also provides the freedom and independence to modify, adapt or integrate its architecture according to specific needs of the stakeholders